Higher education and human development: students’ and graduates’ perspectives from two Tanzanian universities - Kibona, Bertha (University of the Free State, 2020)
Globally, there has been growing recognition of the value and importance of higher education (HE) to individuals, families, and nations. The evidence of this can be seen in the rapid expansion of higher education institutions (HEIs), increased enrolment, the ongoing linking of HE to issues of development, as well as investment directed towards the sector. However, the increasing realisation of the value of HE seems to be aimed predominantly at economic competitiveness and opportunities. This focus has been criticised by some scholars, policymakers, and commentators who argue that HE should also be valued for its potential to advance the non-economic elements that are essential for individual and national flourishing. This argument is premised on the broader idea of HE contributing to human development and/or the public good. Yet, relatively few studies have explored the perspectives of students and graduates on the value of HE, with even less focus on Tanzania. Using human development and the capability approach as analytical framework, this study explores how HE can enhance valued capabilities and promote the well-being of both an individual and the broader society. The study is situated within the pragmatism paradigm in which mixed methods were employed to explore the perspectives of students and graduates. Data was collected through survey questionnaires, semi-structured interviews, focus group discussions, and document analysis from two universities. Data was analysed thematically and statistically. Bearing in mind the socio-economic climate of Tanzania as a developing country, findings from the study indicate that instrumental economic perspectives primarily influence Tanzanian HE. However, there are instances of concern about human development and the public good, especially from the valuable beings and doings mentioned by participants, which involved both economic and social values. Nonetheless, while universities enhanced some of the values, there are persistent factors, including socio-economic background, gender, public policy and teaching and learning that constrained students' or graduates' valuable beings and doings. Based on the empirical findings, the study argues that the conceptualisation and operationalisation of the role of HE needs to be broadened. To fully appreciate the role of HE in human development and the public good, universities need to expand the valued human capabilities by addressing the conversion factors that have constraining effects. This includes: (1) Equitable access to university, including gender equity and students from disadvantaged backgrounds; (2) Updating the curriculum to provide economic opportunities to students and produce whole persons (graduates) for a flourishing economy and meaningful life for all; and (3) Equitable and inclusive education environments for students to participate and achieve their goals. This will not only promote the economic benefits of HE but also contribute to social justice and enhance students' and graduates' capabilities to choose and contribute to the public good and social transformation.
Thesis (Ph.D. (Development Studies))--University of the Free State, 2020
Keywords: Higher education; Human development; Public good; Economic development; Capability approach